Studies on optimization of cultural conditions and effect of media constituents on production of intracellular penicillin V acylase from Erwinia aroideae (DSMZ 30186) - Atul, Kumar; Vivek, Lonkar; Archana, Pundle (Research Journal of Biotechnology, 2008)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme. Erwinia aroideae (DSMZ 30186) produced high levels of intracellular penicillin V acylase. Amongst various carbon sources used (2.0 %); fructose, galactose, sucrose and mannitol increased enzyme production up to 579, 544, 534 and 504 IU/g dry weight (DW), respectively, compared to minimal media (263 IU/g DW); however maximum PVA productivity (2796 IU/ L) was achieved using fructose. Ammonium ions escalated the enzyme production to 1266.9 IU/g DW; however sodium glutamate was the best nitrogen source for overall productivity of enzyme (2045 IU/ L). Cornsteep liquor and skim milk were used as supplements; 1.0 % cornsteep liquor and 3.0 % skim milk were optimum for the production of PVA up to 823 and 93 IU/g DW, respectively. Optimum cultural conditions for the production of PVA from E. aroideae were standardized. Erwinia aroideae produced 1543 IU/g DW penicillin V acylase in Erlenmeyer flasks (250 ml) containing 50 ml of minimal medium with 0.3% ammonium sulphate, pH 7. 0 at 28 degrees C and 180 rpm when incubated for 56 hr.
Keywords: carbon sources; Erwinia aroideae; intracellular; nitrogen sources; Penicillin V acylase